In search of the dimensions of an incandescent light bulb filament - Ladino, Luis Alejandro; Rondon, Hermilda Susana (IOP Publishing Ltd, 2018)
The purpose of this paper is to present and discuss an alternative solution to an experimental problem given to high school students in the XXII Ibero-American Physics Olympiad held by Colombia this year. From the measurements of electric current and potential difference across a small tungsten filament lamp students should find the dimensions of its filament. The results obtained are compared with the ones measured directly. This challenging and low-cost experiment can be easily implemented and carried out in any introductory physics laboratory courses.

El propósito de este trabajo es presentar y discutir una solución alternativa a un problema experimental entregado a estudiantes de secundaria en la XXII Olimpiada Iberoamericana de Física realizada por Colombia este año. A partir de las medidas de la corriente eléctrica y la diferencia de potencial en una pequeña lámpara de filamento de tungsteno, los estudiantes deben encontrar las dimensiones de su filamento. Los resultados obtenidos se comparan con los medidos directamente. Este experimento desafiante y de bajo costo se puede implementar y llevar a cabo fácilmente en cualquier curso de introducción al laboratorio de física.
En busca de las dimensiones de un filamento de bombilla incandescente
Keywords: Corrientes eléctricas; Electric currents; Física - Experimentos; Physics - Experiments